Perceptions of Pre-service Teachers in Coastal Areas Towards Team Project-Based Learning Integrating Digital Technology - Siregar Nur Asma Riani; Susanti Susanti; Elvi Mariyanti (SHS Web of Conferences)
Collaborative learning has become one of the benchmarks for the success of higher education learning. One of the learning strategies involves collaboration among group members in planning and executing a series of learning activities oriented toward completing an assigned project is a team project-based learning strategy. This study aims to explore the pre-service teachers' perceptions in coastal area towards team project-based learning creating virtual teaching aids using the Geogebra Application. The research subjects consisted of 6 pre-service teachers from the coastal areas studying the Plane and Space Geometry course in the Mathematics Education Department of UMRAH. This research is a descriptive study with a qualitative approach. The data was collected using questionnaires, interviews, and documentation techniques. The research data were analyzed using Miles and Huberman's qualitative analysis techniques. The results showed that the overall subjects evaluated the implementation of the team project-based learning was well carried out. Generally, subjects assessed that they were able to develop virtual teaching aids and achieved the learning objective. Students' thinking and collaboration skills develop throughout the implementation of collaborative learning as well as improve their technology literacy. They believe further learning in mastering Geogebra applications is needed to assist them in creating other virtual geometric teaching aids.